Waste Management in the Circular Economy Framework: A Study on Biomass and Compost Potential Production in Payakumbuh City - Afifi, Abdullah A; Arifin, Nor Anisa; Taslapratama, Irwan (IDRIS Darulfunun Institute, 2025)
This study explores the potential of integrating waste management strategies with circular economy principles to enhance biomass and compost production in the greater Payakumbuh area. As regional urbanization and domestic waste levels continue to rise, there is an urgent need to shift from linear waste disposal systems toward resource-oriented waste valorization. This paper proposes a circular model that repositions organic household waste as a green input for local biomass energy and organic fertilizer production, thereby contributing to environmental sustainability, regional agricultural resilience, and green economic development. Drawing on interdisciplinary frameworks from circular economy theory, waste-to-resource models, and regional development planning, the study analyzes the feasibility of composting and anaerobic digestion as localized waste treatment technologies. It also examines governance challenges, infrastructure readiness, and community engagement in the region. The case of Payakumbuh, where agricultural productivity and urban waste generation are closely intertwined, illustrates both the opportunities and constraints of implementing circular economy strategies in smaller Indonesian urban centers. By conceptualizing a closed-loop system tailored to the socio-economic characteristics of Payakumbuh, this research provides a foundation for future empirical studies and policy interventions aimed at sustainable resource management and low-carbon regional transformation.